Dynamic mechanical relaxation behavior of Zr35Hf17.5Ti5.5Al12.5Co7.5Ni12Cu10 high entropy bulk metallic glass. (30th August 2021) - Zhang, L.T.; Duan, Y.J.; Wada, T.; Kato, H.; Pelletier, J.M.; Crespo, D.; Pineda, E.; Qiao, J.C.
Graphical abstract: Highlights: Dynamic mechanical behavior of the non-equiatomic HEBMG was probed by DMA. Dynamic mechanical spectra of HEBMG could be well described by the quasi-point defects theory. The correlation factor is higher than that of conventional metallic glasses ascribed to the high configuration entropy. Abstract: Non-equiatomic high entropy bulk metallic glasses were reported recently and show unique mechanical and physical properties. Dynamic mechanical relaxation behavior of Zr35 Hf17.5 Ti5.5 Al12.5 Co7.5 Ni12 Cu10 high entropy bulk metallic glass was investigated by dynamic mechanical analysis (DMA) and the mechanical spectra could be well described by the quasi-point defects (QPD) theory. Compared to typical metallic glasses, the intensity of the β relaxation of Zr35 Hf17.5 Ti5.5 Al12.5 Co7.5 Ni12 Cu10 high entropy bulk metallic glass is lower due to the sluggish diffusion. At the same time, the correlation factor χ is higher than that of conventional metallic glasses and this is ascribed to the high configuration entropy. In parallel, physical aging below the glass transition temperature leads to a decrease of atomic mobility, caused by a decrease of the concentration of defects.